NIGELLA SATIVA HAS BENEFICIAL EFFECT ON OSTEOPOROSIS AND BONE HEALING. IS IT FACT OR FICTION? A SYSTEMATIC REVIEW - Osman, Muhamed T (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Osteoporosis is the most common reason for a broken bone among the elderly. Several experimental studies have been reported that Nigella sativa (NS) and/or its major component thymoquinone (TQ) have good effects on osteoporosis and bone healing. We conducted this systematic review to evaluate these relevant studies to prove whether NS and/or TQ has potential effect on osteoporosis and can stop pathogenesis of this disease or this matter still just a fiction. A search on published studies was done using databases including Scopus, PubMed, Google Scholar, Web of Science, and CINAHIL. Terms searched included Nigella sativa, black seed, TQ, osteoporosis, bone healing.â€ Initially, 213 articles were extracted. After reviewing their titles and abstracts, 124 articles (Medline, 43; Scopus, 67; EBSCO, 14) were retrieved for further evaluation. However, after excluding the clinical trial studies, human reviews, removal of abstracts and unrelated studies, seven studies were considered finally as eligible for our review. Finally, seven studies were considered eligible for our review. The total number of animals used was 220 (150 rats and 70 rabbits) from different experimental study. Based on the results of this systematic review, we conclude that NS or TQ extract therapy for osteoporosis cannot be recommended yet and these data will not suffice to exclude the beneficial effects of NS on bone turnover reliably. Therefore, more studies are required to explore the specific cellular and molecular targets of NS or TQ using animal osteoporosis models. Once the anti-osteoporotic effectiveness of NS or TQ will be established, human studies can be carried out. Â